TINGKAT KEBERSIHAN GIGI TIRUAN SEBAGIAN LEPASAN RESIN AKRILIK DITINJAU DARI FREKUENSI DAN METODE PEMBERSIHAN - Pocut Aya Sofya; Liana Rahmayani; Fenny Fatmawati (Dentistry Faculty, 2016)
The dirty acrylic resin removable partial denture can destruct remaining mouth structure, halitosis, and bad aesthetic. Acrylic resin removable partial denture can be cleaned by brushing method, soaking, or a combination of both. The level of cleanliness of acrylic resin removable partial denture affected by frequency, the cleaning method, and dentist instructions. The main objective of this study is to determine the level of cleanliness of acrylic resin removable partial denture in terms of frequency and the cleaning method. The subject in this study were 32 people that wear acrylic resin removable partial denture in the residential complex of PT. Arun NGL with purposive sampling technique. This studys scoring was based on Reddick et al studies to determine the level of cleanliness of acrylic resin removable partial denture. The results of this study showed that 100% of the subjects cleaning their denture 3 times a day and 100% of the subjects using the brushing method, in which 53,1% of the subjects wearing clean acrylic resin removable partial denture. The conclution of this study is that all of subject cleaning their denture everyday using the brushing method and the majority of the acrylic resin removable partial denture cleanliness level of subjects is cleaned.Keywords : Cleanliness, Acrylic Resin Removable Partial Denture, Frequency, Method